Monitoring athlete load: Data collection methods and practical recommendations - Wing, C. (Strength and Conditioning Journal, 2018)
Collecting data about athlete load enables support staff to make appropriate changes to an athlete or team's training dose. Through this careful manipulation, athlete injury and illness occurrence can be reduced. Furthermore, athletes can be safely returned to play after injury. There are several data collection methods available which include: rating of perceived exertion, global positioning systems, wellness questionnaires, and heart rate measures. Which ones to adopt and how to implement them within practice can depend on several factors. Ultimately, the way in which the data are used to inform practice is the key to effective load management.